A Study of Dental Visits and Related Factors of Special Needs Patients During the Covid-19 Pandemic - MORIMOTO, Masako; MIYAZAKI, Hironori; YAMAGUCHI, Hisaho; ASAHINA, Hironao; ODA, Yuki; FURUTANI, Chiaki; NAITO, Mariko; NISHIO, Yoshifumi; YOSHIDA, Yuriko; OKADA, Yoshiyuki (Journal of the Japanese Society for Disability and Oral Health, 2023)
Introduction：The novel coronavirus pandemic has had a great impact on all fields around the world. However, there have been no reports on the status of dental visits by special needs patients during the pandemic, and the background of patients who postponed or continued dental visits. Therefore, in this study, we conducted a survey of patients who were scheduled to visit our dental clinic for special needs patients during the declaration of a state of emergency for the pandemic, and aimed to clarify the factors related to deciding whether to visit or not.Subjects and Methods：We conducted a questionnaire survey by mail of 320 patients and their guardians who were scheduled to visit our dental clinic during the period when the state of emergency was declared nationwide. Of the 198 subjects who responded, 185 were analyzed （approved by E-2067, Hiroshima University Epidemiological Research Ethics Committee）.Results：According to the questionnaire survey, about 70% of patients postponed dental visits. There was a significant difference in the presence or absence of anxiety about the oral cavity between the three groups：“the group that postponed on their own judgment,” “the group that postponed due to communication from the university,” and the “continued consultation group.” In addition, there was a significant difference between “with anxiety about the oral cavity” and “postponing dental visits for special needs patients during the declaration of a state of emergency.”Discussion and Conclusion：It was suggested that postponing dental visits increased anxiety about the oral cavity among patients and guardians. In the future, it is important to create a system that does not interrupt dental visits for special needs patients.